Dominasi Patriakhi dan Marginalisasi Tokoh Perempuan Subaltern dalam Novel Lail wa Qudbhan Karya Najib Al-Kailani - Rahimal Khair; Hidia Tarauni (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This article examines the forms of domination and marginalization of subaltern female characters in the novel Lail wa Qudhban by Najib al-Kailani, using a postcolonial literary criticism approach, especially Gayatri Chakravorty Spivak's subaltern theory. This research uses a qualitative-descriptive method through critical reading techniques and textual analysis. The primary data in this research is the novel Lail wa Qudbhan by Najib al-Kailani. In contrast, the secondary data in this research are books, scientific works containing Gayatri Chakravorty Spivak's postcolonial and subaltern theory, Najīb al-Kaylānī's biography and thoughts, and relevant references, both previous studies or research on this novel. Data collection uses documentation techniques, hermeneutic reading, and recording and classification of quotations. The data analysis technique uses descriptive-analytical. The results of the study show that the female character (Inayat) in the novel experiences structural and layered domination and marginalization, which originates from four main factors: (1) gender-biased interpretation of religious teachings, (2) customs that legitimize inequality, (3) social construction that silences women, and (4) negative stereotypes against women. The character of Inayat in the novel is presented as a subject who experiences symbolic and social limitations, but at the same time has hidden potential for resistance. This study emphasizes the importance of a postcolonial approach in revealing the layers of power hidden behind the representation of women in modern Arabic literature.